Melinnopsis angolensis (Annelida: Polychaeta: Ampharetidae), a new species from the Angola Basin. - Hilbig, Brigitte (Organisms Diversity & Evolution, 2005)
A new species of ampharetid polychaetes, Melinnopsis angolensis sp. nov. is described. It was collected with an Agassiz trawl at seven stations in the Angola Basin in depths between 5385 and 5448 m. The new species differs from the few other species described in this genus by the number of thoracic setigers, the number of enlarged tentacles, presence of reduced notosetae in the anterior thorax, and morphological details of the gills and postbranchial membrane. A brief overview of the other species of the genus is given, and the synonymization of Amelinna and Melinnopsides with Melinnopsis is discussed.
AnnelidaBase. Open access article.